Mechanism of Puerarin-Polybutyl Cyanoacrylate Nanoparticles on Apoptosis of Brain Cells in Rats with Cardiac Arrest/Cardiopulmonary Resuscitation - Xue Zhao; Yuanshen Xu; Jinyan Fang (Journal of Animal and Plant Sciences, 2025)
Following cardiac resuscitation, cerebral perfusion pressure increases, accompanied by impaired autoregulation of cerebral blood vessels, which subsequently leads to cerebral reperfusion congestion and resultant brain injury. This study aimed to explore the therapeutic mechanism of puerarin (PARI) nanoparticles (NPs) on cardiopulmonary resuscitation after cardiac arrest in rats. PARI-polybutyl cyanoacrylate NPs (PARI-BCA-NPs) were fabricated using PARI as the model drug. While the NPs were physically characterized, the pharmacokinetics and tissue distribution of the intravenously administered drug in rats were studied. Subsequently, a rat cardiac arrest/cardiopulmonary resuscitation (CA/CPR) model was established to evaluate the protective effect of the nanodrug on brain cells. At the same dose, injection of the PARI-BCA-NP solution significantly altered the pharmacokinetic properties, increasing the mean drug retention time, blood concentration, and area under the curve (AUC) by 54% compared to the PARI injection (P<0.05). Relative to the PARI injection group, the AUC of each tissue injected with PARI-BCA-NP solution was increased drastically, and the AUC of the brain tissue injected with the NP solution was 2.72 times that of the brain tissue injected with the PARI parent drug group. Based on the CA/CPR model, rats were grouped (sham operation group, model group, and NP group). The fluorescence intensities of superoxide dismutase (SOD)1 and SOD2 in the NP group at each time point were markedly increased versus the model group (P<0.05), and positive rates of TUNEL and Caspase3/TUNEL were decreased, i.e., the apoptosis rate of brain cells was decreased (P<0.05). PARI-BCA-NPs exhibit excellent pharmacokinetic properties and significantly improve brain injury caused by CA/CPR by reducing oxidative stress and neuronal apoptosis in brain tissue. They demonstrate promising therapeutic potential in animal models, particularly in the intervention of brain injury following CA. Further research will help explore their applicability, especially their feasibility in acute-phase treatment, offering a novel therapeutic strategy.
Keywords: puerarin; PARI-BCA-NPs; pharmacokinetics; brain cell apoptosis